2021
DOI: 10.18280/ijdne.160108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Doses of Green Manure from Different Sources on Growth and Yield of Maize in Dryland

Abstract: Dryland has low soil fertility. Efforts that can be made to improve soil fertility are fertilizer technologies such as green manure compost. The aim of this study was to determine the type and dose of green manure to increase the growth, production and nutrient uptake of maize in the dryland. The research was conducted in Sidera Village Sigi Biromaru District, Sigi Regency, Central Sulawesi from June to December 2018. The research used a factorial randomized block design. The first factor is the type of green … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…Sources of organic material can be compost, green manure, manure, crop residues, livestock waste, industrial waste using agricultural materials and organic waste. Organic fertilizers can be solid or liquid which are used to increase vegetative growth (Kandil et al, 2013) and yields (Idham et al, 2021;Petrovic et al, 2020). Also, it plays a role in providing nutrients to the soil by improving the physical, chemical and biological properties of the soil (Müjdeci̇ et al, 2020) and the efficiency of using fertilizers (Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sources of organic material can be compost, green manure, manure, crop residues, livestock waste, industrial waste using agricultural materials and organic waste. Organic fertilizers can be solid or liquid which are used to increase vegetative growth (Kandil et al, 2013) and yields (Idham et al, 2021;Petrovic et al, 2020). Also, it plays a role in providing nutrients to the soil by improving the physical, chemical and biological properties of the soil (Müjdeci̇ et al, 2020) and the efficiency of using fertilizers (Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The application of organic fertilizer in the experimental demonstration plot was seen to increase the vegetative growth of rice plants in contrast to land that was not given any organic fertilizer. This is supported by research (Lasmini et al, 2021), (Lasmini et al, 2022) and (Idham et al, 2021) that the application of organic fertilizers both solid and liquid can increase the vegetative growth of plants. In addition, organic fertilizers also play a role in providing nutrients to the soil and making efficient use of fertilizers and substituting inorganic fertilizers (Yang et al, 2020).…”
Section: B Formulation Of Bio-rational Insecticidesmentioning
confidence: 88%
“…Karkush et al [10] studied the effect of magnetic fields on water and reported that magnetic fields in water could change several properties such as pH, surface tension, electrical resistivity, viscosity, and inhibition of calcite formation. The characteristics of water flow are very capable of increasing plant growth [31]. It was further reported that a 2000 G magnetic field for more than 24 hours made the pH of the water rise from 6.4 to 8.6.…”
Section: Discussionmentioning
confidence: 99%